Penggunaan Teknologi dalam Pembelajaran Bahasa Inggris: Studi Kasus Implementasi Aplikasi E-Learning - Dian Yuliani Paramita, Putu (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims at the Use of Technology in English Language Learning: Case Study of E-Learning Application Implementation. The method used in this research is Systematic Literature Review. Data collection techniques with documentation from Google Schoolar. Data analysis with critical review. Implementation of e-learning applications in English learning has great potential to increase the effectiveness and accessibility of education. In this case study, technology is used as a tool to integrate English learning materials interactively and flexibly. As a result, students can access learning resources anytime and anywhere, increasing their participation and engagement in the learning process. In addition, e-learning applications also enable more efficient monitoring and assessment of student progress. However, the success of this implementation relies heavily on good design, user training, and adequate technical support to maximize the potential of learning English through this technology.